2009
DOI: 10.1111/j.1467-9590.2009.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Exactly Solvable Model for Nonlinear Pulse Propagation in Optical Fibers

Abstract: The nonlinear Schrödinger (NLS) equation is a fundamental model for the nonlinear propagation of light pulses in optical fibers. We consider an integrable generalization of the NLS equation, which was first derived by means of bi-Hamiltonian methods in [1]. The purpose of the present paper is threefold: (a) We show how this generalized NLS equation arises as a model for nonlinear pulse propagation in monomode optical fibers when certain higher-order nonlinear effects are taken into account; (b) We show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
125
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 22 publications
(64 reference statements)
3
125
0
1
Order By: Relevance
“…The FLE is a partial differential equation that has been derived as a generalization of the NLSE [26,27]. In the context of optics, the FLE models the propagation of ultrashort nonlinear light pulses in monomode optical fibers [27].…”
Section: Fokas-lenells Equationmentioning
confidence: 99%
“…The FLE is a partial differential equation that has been derived as a generalization of the NLSE [26,27]. In the context of optics, the FLE models the propagation of ultrashort nonlinear light pulses in monomode optical fibers [27].…”
Section: Fokas-lenells Equationmentioning
confidence: 99%
“…This equation is related to the nonlinear Schrödinger (NLS) equation in the same way that the Camassa-Holm equation is associated with the KdV equation [34].The Fokas-Lenells equation is a completely integrable equation which has been derived as an integrable generalization of the NLS equation using bi-Hamiltonian methods [35]. In optics, the FL equation models the propagation of nonlinear light pulses in monomode optical fibers when certain higher order nonlinear effects are taken into consideration [36]. The complete integrability of the FL equation has been exhibited by using the inverse scattering transform (IST) method [37].…”
Section: Open Accessmentioning
confidence: 99%
“…Related results can also be directly applied to (1.1) and (1.3) since the existence of these simple transformations among them. It is shown that (1.4)/(1.5) is a completely integrable nonlinear partial differential equation possessing Lax pair, bi-Hamiltonian structure, and soliton solutions [5,[16][17][18]. One of the most remarkable feature of the FL equation is that it possesses various kinds of exact solutions such as solitons, breathers, etc..…”
Section: Introductionmentioning
confidence: 99%
“…An important feature of equation (1.3) is that it describes the firs negative fl w of the integrable hierarchy associated with the derivative nonlinear Schrödinger (DNLS) equation [5,12,13,16]. In this paper, we consider the following complexifie version of FL system q xt − q xx + iqq x r − 2iq x + q = 0, r xt − r xx − iqrr x + 2ir x + r = 0, (1.4) which is exactly reduced to the FL equation (α = β = 1 in (1.2)) q xt − q xx ∓ i|q| 2 q x − 2iq x + q = 0, (1.5) for r = ±q.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation